Intellectual property and trade secrets - Arowosaiye, Yusuf Ibrahim; Masum, Ahmad; Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (LexisNexis Malaysia Sdn Bhd, 2025)
Our preoccupation in this chapter is to attempt an overview of Intellectual Property (‘IP’) and focus on trade secrets and their commercial value to businesses. In doing this, it is imperative to distinguish the general notion of intellectual property as comprising copyright, industrial designs, patents, trademarks, etc., from the notion of trade secrets. Although it is indisputable that trade secrets come under the ambit of intellectual property rights, they have a distinct nature from other typologies of IP. This must have been responsible while our definition of IP above overlooks the significance of ‘“trade secrets’.” In the U.S., for example, intellectual property commonly refers to patents, trademarks, copyrights, and trade secrets. Trade secrets, as a form of intellectual property, connote confidential business information, including any business practice or process, which is generally not known to others and gives the company an economic advantage over its competitors.